Этика: учебник для студентов вузов / А. А. Гусейнов, Р. Г. Апресян - Гусейнов Абдусалам Абдулкеримович (Disciplinae, 1999)
Экземпляры: ЧЗ (20160121) / Инвентарный номер: 34613 / Цена: 58.00 / Сис.шифр: 87.7 / Авт.знак: Г 96 / ГРНТИ: 02.51 / ББК: 87.7 я73